A bioinspired thiolate-bridged dinickel complex with a pendant amine: synthesis, structure and electrocatalytic properties. Issue 7 (29th January 2020) - Sun, Puhua; Yang, Dawei; Li, Ying; Wang, Baomin; Qu, Jingping
Abstract : A bioinspired thiolate-bridged dinickel complex featuring a pendant amine realizes electrocatalytic hydrogen evolution at a relatively low overpotential. Abstract : By employing X(CH2 CH2 S − )2 (X = S, tpdt; X = O, opdt; X = NPh, npdt) as bridging ligands, four thiolate-bridged dinickel complexes supported by phosphine ligands, [(dppe)Ni(μ-13κSSS′:22κSS-tpdt)Ni(dppe)][PF6 ]2 (1[PF6 ]2, dppe = Ph2 P(CH2 )2 PPh2 ), [(dppe)Ni(μ-13κSSN:22κSS-npdt)Ni(dppe)][PF6 ]2 (2[PF6 ]2 ) and [(dppe)Ni( t -Cl)(μ-13κSSX:22κSS-C4 H8 S2 X)Ni(dppe)][PF6 ] (3[PF6 ], X = S; 4[PF6 ], X = O) were facilely obtained by the salt metathesis reaction. These four thiolate-bridged dinickel complexes have all been fully characterized by spectroscopic methods and X-ray crystallography. In 2[PF6 ]2, elongation of the Ni–N bond distance, possibly caused by steric hindrance, indicates that the pendant nitrogen group shuttles between the two nickel centers in solution, which is evidenced by 31 P{ 1 H} NMR spectroscopic results. Furthermore, these thiolate-bridged dinickel complexes have all been proved to be electrocatalysts for proton reduction to hydrogen. Notably, complex 2[PF6 ]2 featuring a pendant amine group in the secondary coordination sphere exhibits the best catalytic activity at a relatively low overpotential.